Passampo Siri' in the Bugis Marriage Practies in East Kolaka, Indonesia: A Sociological Perspective of Islamic Law - Ipandang, Ipandang; Darlis, Syamsul (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2022)
This research aims to illustrate the problematics of Passampo Siri’ marriage practice in the Bugis community, East Kolaka Regency, using a descriptive qualitative method based on the sociology of Islamic law. Data collection techniques involve interviews with informants deemed necessary and observing or directly paying attention to the implementation of the marriage tradition through siri'. The findings indicate that the Bugis society practices this type of marriage because of social pressure to conceal shame, adherence to ancestral customs, a lack of public understanding of relevant marriage law norms, and low levels of public education. However, the custom is no longer practiced since it cannot provide justice and order in society. This marriage also has implications for acts against the law of society, as stipulated in Article 53 of the KHI that a pregnant woman out of wedlock can only be married to a man who impregnates her. In contrast, for the practice of Passampo Siri’ marriages, the pregnant woman out of wedlock is married to another man. Therefore, this research contributes directly to the development of the study of Islamic law in Indonesia and the world in finding the best solution to achieving legal expectations among the public, especially regarding marriages of pregnant women out of wedlock with men who do not impregnate them.